Epidemiological Characteristics of Autism in Republic of Macedonia - Trajkovski, Vladimir; Vasilevska, Kristin; Ajdinski, Ljupcho; Spiroski, Mirko (Faculty of Philosophy, UKIM, Skopje, Macedonia, 2005)
Infantile autism is pervasive developmental disorder with abnormal or damaged psychical development manifested after the second or third year of life, with characteristics in the shift of pathological functioning in the sphere of social interactions, in communications with the environment, and with repetitive behavior. The aim of this article is to show a part of demographic and epidemiological characteristics of the population with autism registered in the Republic of Macedonia.This research is a retrospective study, followed on the territory of the Republic of Macedonia, which covered 50 people with autism. All examined people have a verified diagnosis according to ICD-10 classification of diseases and DSM-IV criteria made in the special educational and medical institutions in our country. From the analysis of examined autistic people in the sample it has confirmed that the prevalence of autism in RM is 0.25 people up to 10.000 inhabitants. The male gender is 2.5 times more frequent than the female gender. The mean age of patients is 11 years. The socio-economic condition does not take part in the genesis of autism. The season of birth is not connected with the appearance of the disturbance. Data for mothers disease during the pregnancy (p=0.04), as well as the pathological course of the pregnancy (p=0.02) is a risk factor for appearance of the syndrome. The pathological delivery and the complications in the perinatal period are not the risk factors in this study (p>0.05). The duration of nursing and the preliminary rejection of mother’s milk are significantly associated with the appearance of autism (p<0.01). The results from this study may be useful as a good base for further epidemiological researching, revealing new risk factors in the genesis of autism, and for planning the prevention of this severe syndrome.
Епидемиолошки карактеристики на аутизмот во Република Македонија
Keywords: autism, epidemiological characteristics, Republic of Macedonia